1988
DOI: 10.1111/j.1432-1033.1988.tb14463.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the bovine k‐casein gene

Abstract: 1. The bovine ti-casein gene has been isolated as a series of overlapping I clones and shown to consist of five exons distributed over a total length of approximately 13 kb. Most of the mature protein-coding sequence is contained in a single large exon.2. Approximately 65% of the gene has been sequenced together with portions of the 5'-and 3'-flanking sequences. The immediate 5'-flanking sequence contains several motifs which are characteristic of upstream regions including a TATA box, a CAAT box, a sequence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
76
0
7

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(87 citation statements)
references
References 40 publications
(16 reference statements)
2
76
0
7
Order By: Relevance
“…Os quatro genes da caseína estão mapeados no cromossomo 6, em cabras, enquanto os genes para α-lactalbumina e β-lactoglobulina foram mapeados no cromossomo 5 (Hayes et al, 1993). O gene da κ-caseína tem efeito positivo sobre a produção de proteína do leite e também é importante para a estrutura e a estabilidade das micelas de caseína, que aumentam o conteúdo de proteína total nos derivados do leite e a eficiência na produção de queijo (Alexander et al, 1988).…”
Section: Introductionunclassified
“…Os quatro genes da caseína estão mapeados no cromossomo 6, em cabras, enquanto os genes para α-lactalbumina e β-lactoglobulina foram mapeados no cromossomo 5 (Hayes et al, 1993). O gene da κ-caseína tem efeito positivo sobre a produção de proteína do leite e também é importante para a estrutura e a estabilidade das micelas de caseína, que aumentam o conteúdo de proteína total nos derivados do leite e a eficiência na produção de queijo (Alexander et al, 1988).…”
Section: Introductionunclassified
“…Therefore, the κ-casein gene (CSN3) is unlikely to be completely free of selective constraints (Ward et al, 1997). Interspecies comparisons have demonstrated that CSN3 possesses the highest degree of conservation among the casein genes, which may be related to its essential function as a stabilizer of casein micelles (Alexander et al, 1988). On the other hand, high intraspecies variability has been reported for CSN3 in cattle (for a review see Formaggioni et al, 1999) and, more recently, in goats.…”
Section: Introductionmentioning
confidence: 99%
“…The kappa-casein gene is situated on bovine chromosome 6 and encodes milk protein important for the structure and stability of casein micelles (Alexander et al, 1988). Polymorphism of the kappa-casein gene has been known since 1964 (Neelin, 1964), and nine alleles are known in all.…”
mentioning
confidence: 99%